A Note on Physical and Mechanical Properties of Terminalia paniculata (Kindal) from Kerala - Jain, J. D.; Dangwal, M. N. (Indian Forester, 1985)
PhYSical and mechanical properties of Terminalia peniculata (Kindal) received from Karulai Range, Nilambur, Kerala tested in green condition have been reported and discussed. The results obtained have been compared with standard teak. It is found that values are lower than standard teak in general. Expected values based on the strength-specific gravity formulae have also been reported for comparison.